Analisis Terhadap Gaji Buruh dalam UU No. 6 Tahun 2023 Perspektif Maqāṣid Syarīʻah Ibnu ‘Āsyūr - Alhaddad, Muhammad Idris; Hakim, Nur (Syariah: Journal of Fiqh Studies, 2024)
UU no. Year 11, 2020, concerning the Working Section, was declared conditionally unconstitutional by the Constitutional Court for two years and must be corrected by the law-drafting body. To hear the Constitutional Court's decision, the government issued Perppu No. 2 of 2022, concerning the Ciptaker. On March 31, 2023, Perppu was ratified under Law No. 6 of 2023. However, according to the president of the Labour Party, Ir. H. Said Iqbal, S.T., and M. E. stated that UU has the right to pay a minimum price. I have nothing to do with the Ramadan Problem. The legal construction of Law No. Year 6, 2023: Concerning Work on Workers ' Salaries in Indonesia. Second, what is the perspective of Ibn ʻĀsyūr's maqaṣid syarīʻah regarding workers' salaries based on Law no. 6 of 2023 concerning work. This research aims to analyze Ibn ʻĀsyūr's maqaṣid syarīʻah thoughts regarding workers' salaries based on Law no. 6 of 2023 concerning work. To achieve these objectives, qualitative descriptive research was conducted through a literature review using a legal hermeneutical analysis. As a result, in terms of legal construction, there are articles regarding the procurement and remuneration of wages that are controversial, namely Article 88C paragraph (2), Article 88D paragraph (2), and Article 88F. When the house was closed, Ibn ʻĀsyūr, regarding workers' salaries based on law, stated that the government was obliged to establish minimum wage regulations to ensure a living wage for workers.